Bis(dimethyl sulfoxide-κO)bis(mercaptoacetato-κ2O,S)tin(IV) - Li Song (Acta Crystallographica Section E, 2009)
In the title compound, [Sn(C2H2O2S)2(C2H6OS)2], the mercaptoacetato ligands chelate to SnIV through S and one O atoms. The metal centre is also coordinated by two dimethyl sulfoxide (DMSO) ligands through the O atom, leading to an overall distorted octahedral coordination environment for the SnIV atom. The molecular adduct lies on a twofold rotation axis.